Factors Influencing Impulse Purchases of Fashion Products with the Model of Theory of Planned Behavior in the Muslim Millennial Generation - Mamun sarma; Irni johan; Tresna Mutiara (Green Publisher Indonesia, 2025)
The rapid development of digital technology has transformed the marketing landscape and consumer behavior, especially after the Covid-19 pandemic. Indonesian consumers increasingly engage in online shopping, with a significant surge on e-commerce platforms. Fashion products have become one of the most dominant categories, now serving as both a lifestyle and psychological need, driving impulsive purchases. E-commerce platforms employ aggressive promotional strategies such as discounts and free shipping to attract buyers. In response to these changes, businesses must adopt a deeper understanding of consumer behavior through approaches like the Theory of Planned Behavior, including consideration of religiosity as a factor influencing impulsive buying tendencies. This research aims to analyze the influence of attitude, subjective norms, perceived behavioral control, and religiosity on impulsive buying intention, as well as the impact of impulsive buying intention on impulsive buying behavior. The Theory of Planned Behavior (TPB) serves as the theoretical foundation, with religiosity included as a moderating variable. The study employs Structural Equation Modeling - Partial Least Squares (SEM-PLS) to examine the relationships between attitude, subjective norms, perceived behavioral control, religiosity, impulsive buying intention, and impulsive buying behavior. This technique is chosen for its ability to explain variable variance and simultaneously assess both measurement and structural models. Data were collected through an online survey targeting muslim millennials in the Greater Jakarta area (Jabodetabek) who actively purchase fashion products through e-commerce.